Analisis Pengaruh Kepemimpinan, Budaya Organisasi, Motivasi Kerja terhadap Kinerja Organisasi dengan Kepuasan Karyawan sebagai Variabel Intervening (Suatu Kajian Studi Literatur Manajemen Sumber Daya Manusia) - Antonius Ndeok, Yohanes; E.H.J. FoEh, John; A. Manafe, Henny; Sia Niha, Simon (Dinasti Review Publisher, 2023)
Good organizational performance can be achieved if it is supported by employees who are driven by responsible leaders. In addition to leadership factors, organizational performance is also influenced by other factors, such as organizational culture, work motivation and job satisfaction, as well as other factors. The results of this study are 1) Leadership has a positive impact and is quite important for organizational performance; 2) Organizational culture has a positive or significant impact on organizational performance; 3) Work motivation has a positive and important impact on organizational performance; 4) Leadership has a positive and significant impact on employee satisfaction 5) Organizational culture has a positive or significant impact on employee satisfaction; 6) Work motivation has a positive or significant impact on employee satisfaction; 7) Employee satisfaction has a positive or significant impact on organizational performance; 8) Leadership, organizational culture, work motivation have a positive or significant impact on employee satisfaction; 9) Leadership, organizational culture, work motivation have a positive or significant impact on organizational performance.